2021
DOI: 10.2147/oajc.s324678
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Rights-Based Family Planning from 2020 to 2030

Abstract: Introduction An assessment in 2019 by Family Planning 2020 of progress on rights-based family planning since 2012 highlighted the development of tools and guidelines that identify and explain rights in relation to family planning, promotion of rights-based approaches to programing, strengthened accountability, and measurement of rights-focused outcomes. The assessment was also forward-looking, asking what aspects of rights-based family planning still need attention moving from 2020 to 2030. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In a review of indicators of youth-friendly health care, researchers found that there remains debate over the most important dimensions of AYSRH service quality and that many indicators reflect basic health care quality standards that are not specific to AYSRH [ 9 ]. More recently, during an assessment of FP2020’s contributions to advancing rights-based family planning, family planning specialists noted that there remains work to be done in building out indicators that facilitate program measurement, especially at the subnational level [ 33 ]. Indeed, while FP2030 has debuted a comprehensive results framework, few of the proposed indicators offer immediately actionable information to clinic- or district-level program managers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of indicators of youth-friendly health care, researchers found that there remains debate over the most important dimensions of AYSRH service quality and that many indicators reflect basic health care quality standards that are not specific to AYSRH [ 9 ]. More recently, during an assessment of FP2020’s contributions to advancing rights-based family planning, family planning specialists noted that there remains work to be done in building out indicators that facilitate program measurement, especially at the subnational level [ 33 ]. Indeed, while FP2030 has debuted a comprehensive results framework, few of the proposed indicators offer immediately actionable information to clinic- or district-level program managers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…FP2020 is currently renamed FP2030. It is a global partnership that started at the London summit of 2012, trying to promote Rights-based family planning globally with headquarters in the USA (24).…”
Section: London Family Planning Summit 2012mentioning
confidence: 99%
“…Correct use can significantly improve women’s reproductive health and well-being. 2 Contraception can be said to be an important measure of unintended pregnancy, abortion and STI, especially the young people. Recent efforts, in the last decade, have sought to reduce unmet needs among women and girls.…”
Section: Introductionmentioning
confidence: 99%